2009
DOI: 10.1134/s1068162009060065
|View full text |Cite
|
Sign up to set email alerts
|

New polypeptide components from the Heteractis crispa sea anemone with analgesic activity

Abstract: Two new polypeptide components which exhibited an analgesic effect in experiments on mice were isolated from the Heteractis crispa sea tropical anemone by the combination of chromatographic methods. The APHC2 and APHC3 new polypeptides consisted of 56 amino acid residues and contained six cysteine residues. Their complete amino acid sequence was determined by the methods of Edman sequencing, mass spectrometry, and peptide mapping. An analysis of the primary structure of the new peptides allowed for their attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 20 publications
1
57
0
3
Order By: Relevance
“…It plays an important protective role against elastase, which releases in infectious inflammation centers upon neutrophil degranulation. HCPs are able to suppress an inflammation process and pain sensation [3][4][5][6][7][8]. To highlight the mechanism of their influence on inflammation, structures of molecular complexes of HCPs with HNE as a key inflammation enzyme have to be generated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It plays an important protective role against elastase, which releases in infectious inflammation centers upon neutrophil degranulation. HCPs are able to suppress an inflammation process and pain sensation [3][4][5][6][7][8]. To highlight the mechanism of their influence on inflammation, structures of molecular complexes of HCPs with HNE as a key inflammation enzyme have to be generated.…”
Section: Resultsmentioning
confidence: 99%
“…Ovchinnikov Institute of Bioorganic Chemistry of the Russian Academy of Sciences, we had shown that HCPs Jn-IV, APHC1, APHC2, and APHC3 inhibit serine proteinases trypsin and chymotrypsin [3][4][5]. Recently it was found that APHC1, 2, and 3 are able to modulate function of pain vanilloid TRPV1 receptor revealing analgesic effects in vivo [4][5][6][7]. These polypeptides were latter shown to possess with an anti-inflammatory activity in experiments with mice [8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its moderate apparent affinity and low potency, systemic administration of APHC1 induced analgesic activity without producing hyperthermia in rodents during pain-related behavioral tests (Andreev et al, 2008). These findings were extended to other related peptides found in H. crispa, including APHC2 andAPHC3, both of which display analgesic activity in rodents (Kozlov et al, 2009). Interestingly, even though APHC1 and APHC3 differ in only 4 of 56 amino acids, only APHC3 is able to inhibit low pH-mediated activation of TRPV1 channels (Andreev et al, 2013).…”
Section: Peptide Toxins As Trpv1 Channel Modulatorsmentioning
confidence: 69%
“…Studies of protease inhibitors of Heteractis crispa in the Laboratory of Peptide Chemistry (Pacific Institute of Bioorganic Chemistry, Far East Branch, Russian Academy of Sciences) and the Laboratory of Neurore ceptors and Neuroregulators (Institute of Bioorganic Chemistry, Russian Academy of Sciences) demon strated for the first time that, apart from trypsin inhi bition, polypeptides APHC1, APHC2, and APHC3 are able to inhibit the vanilloid pain receptor TRPV1 in vitro and exert analgesic effects in vivo [22][23][24]. For example, in experiments with the TRPV1 receptors expressed in Xenopus laevis oocytes, and in models of pain stimulation in mice, including chemical stimula tion with capsaicin and heat stimulation, it was dem onstrated that, despite the incomplete (~35%) inhibi tion of the receptor function, analgesic polypeptides APHC1 and APHC3 block the pain signal transduc tion [22,23].…”
mentioning
confidence: 99%